Elastic ankle muscle-tendon interactions are adjusted to produce acceleration during walking in humans - Farris, D. J.; Raiteri, B. J. (The Journal of Experimental Biology, 2017)
Humans and other cursorial mammals have distal leg muscles with high in-series compliance that aid locomotor economy. This muscle-tendon design is considered sub-optimal for injecting net positive mechanical work. However, humans change speed frequently when walking and any acceleration requires net positive ankle work. The present study unveiled how the muscle-tendon interaction of human ankle plantar flexors are adjusted and integrated with body mechanics to provide net positive work during accelerative walking. We found that for accelerative walking, a greater amount of active plantar flexor fascicle shortening early in the stance phase occurred and was transitioned through series elastic tissue stretch and recoil. Reorientation of the leg during early stance for acceleration allowed the ankle and whole soleus muscle-tendon complex to remain isometric while its fascicles actively shortened, stretching in-series elastic tissues for subsequent recoil and net positive joint work. This muscle-tendon behaviour is fundamentally different from constant-speed walking, where the ankle and soleus muscle-tendon complex undergo a period of negative work to store energy in series elastic tissues before subsequent recoil, minimizing net joint work. Muscles with high in-series compliance can therefore contribute to net positive work for accelerative walking and here we show a mechanism for how in human ankle muscles.